RADICAL ISLAM IN UZBEKISTAN: PAST AND FUTURE - TODUA, Zurab (CENTRAL ASIA AND THE CAUCASUS, 2005)
For religious extremists Uzbekistan is the most desirable aim in Central Asia because of its favorable geostrategic location, high economic potential, and the rapidly growing population. Control over it would allow the Islamists to deliver a serious blow to contemporary civilization and to lay the cornerstone of the Islamic Caliphate. Since the early 1990s Tashkent has been engaged in a difficult struggle against religious extremists. At first it was fighting alone under fire of human rights and other democratic organizations convinced that the opposition was treated with unjustified cruelty. It was as early as 1997 that President of Uzbekistan Islam Karimov spoke about the dangers of dismissing lightly Islamic fundamentalism and its threats and said that the media abroad had been saying for some time that the Uzbek leaders invented the threat to scare the West for the reasons of their own. Western analysts and experts in Islam readily embraced the idea that fundamentalism was absolutely harmless for the world community and was the headache of "its own” states alone. They even believed that had the Islamists managed to adjust the local regimes to their patterns they would have readily entered into a dialog with the rest of the world. These people proceeded from the fact that many of the fundamentalists were educated in Europe and America. One is tempted to ask them: Do you understand the real state of affairs in the Muslim East repeatedly subjected to disintegration, dissent, and humiliations?1Time has shown that the Uzbek leader was right. Tashkent recognized the threat of religious extremism earlier than any other capital; Moscow arrived at this conclusion in 1999, while the West awoke to this fact in the wake of 9/11. This explains why Tashkent proved to be better prepared to rebuff extremist expansion.